2017
DOI: 10.3138/jvme.0316-055r
|View full text |Cite
|
Sign up to set email alerts
|

Vocation, Belongingness, and Balance: A Qualitative Study of Veterinary Student Well-Being

Abstract: An elevated risk for suicide among veterinarians has stimulated research into the mental health of the veterinary profession, and more recently attention has turned to the veterinary student population. This study sought to qualitatively explore UK veterinary students' perceptions and experiences of university life, and to consider how these may impact upon wellbeing. Semi-structured interviews were conducted with eighteen students from a single UK school, who had been purposively selected to include male, fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…The breadth and factorial pattern of the motivations included in the final derived instrument generally support the motivational taxonomy and conclusions of the precursor exploratory study by Cake et al ,9 namely that there are multiple strong motivations for veterinary work including, but clearly not limited to, early vocational identity and affinity for animals. This only partially supports the predominant view from earlier literature that the major veterinary career motivations are a strong sense of vocational identity1–6 developed alongside a love of animals 1–4 7. While vocational identity was indeed found to be correlated with animal orientation and endorsed as a career motivation by a large subset, identity-based motivations were rejected by over a quarter of respondents and rated significantly lower by younger and recently graduated veterinarians.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The breadth and factorial pattern of the motivations included in the final derived instrument generally support the motivational taxonomy and conclusions of the precursor exploratory study by Cake et al ,9 namely that there are multiple strong motivations for veterinary work including, but clearly not limited to, early vocational identity and affinity for animals. This only partially supports the predominant view from earlier literature that the major veterinary career motivations are a strong sense of vocational identity1–6 developed alongside a love of animals 1–4 7. While vocational identity was indeed found to be correlated with animal orientation and endorsed as a career motivation by a large subset, identity-based motivations were rejected by over a quarter of respondents and rated significantly lower by younger and recently graduated veterinarians.…”
Section: Discussionsupporting
confidence: 57%
“…Rather, graduates stated a broad range of reasons for becoming a veterinarian in addition to animal-oriented identity, including themes such as love of learning, challenge and problem-solving, variety, social relatedness, helping people, social contribution, and career opportunity. An interview-based qualitative study in the UK found similar themes of intrinsic interest in scientific problem-solving and navigating belongingness 6…”
Section: Introductionmentioning
confidence: 98%
“…We included well-being factors to determine how much of the student week quality score was related to noncurricular factors and to identify the level of selected healthy practices. 9 In-class hours and types of activities (examinations, discussions, lectures, etc.) were added to the data to create a more complete picture of the week and for correlation with the week quality and integration scores.…”
Section: Part 4: Student Well-being Factorsmentioning
confidence: 99%
“…Various noncurricular factors have shown to be stressors and protectors of student well-being. 4,8,9 Because our data showed relatively high levels of dissatisfaction with the curriculum and with apparent differences between cohorts, questions about potential well-being factors were added to the survey over time. Data were collected to answer Questions 4a and 4b.…”
Section: Part 4: Student Well-being Factorsmentioning
confidence: 99%
“…The fact that many students mentioned additional benefits such as experiencing fun, relaxation and stress relief through participation in the exercise program is an interesting 'side effect' since stress-related disorders are common amongst veterinary students world-wide. [37][38][39][40][41][42][43][44][45] The Center for Disease Control (CDC) declares exercise to be one of the most important activities to improve physiological as well as psychological health. 46,47 Psychological benefits of exercising include a reduced risk for depression and anxiety, improved mood, better sleep quality, and better cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%